JENDRAL ABDUL HARIS NASUTION PAHLAWAN INTELEKTUAL - Diansyah, Arfan; Manurung, Doni Jeremia; Hastatik, Hastatik; Dwitama, Ridho Iqbal; Iqwadan, Rayhan; Yusraini, Rina (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This article aims to find out the profile of an intellectual hero, Abdul Haris Nasution. To obtain the necessary data, researchers used historical research methods consisting of four stages, namely, heuristics, source criticism, data interpretation and historiography. Then the data collection technique is done with literature studies through books, journals and articles available on the internet, as well as documentation by collecting supporting images or photos. The results showed that Abdul Haris Nasution was the initiator of the dual function of ABRI and the foundation of his guerrilla warfare as outlined in the book Gerilya Principles during the Dutch military aggression at that time to break the Dutch attack. The war is known to attack suddenly, then disappear quickly before the enemy has time to counterattack. Apart from being the originator of guerrilla warfare, Abdul Haris Nasution also contributed to the dual function of ABRI by formulating the dual function of ABRI, which was then known as the "Middle Way". On the night of 30 September 1965, he was one of the Army officers who almost became a casualty of the G30SPKI. He was the main target who managed to escape the operation. The targeting of A.H Nasution was inseparable from his attitude and views towards the Indonesian Communist Party (PKI). During an attack by the PKI on his residence, A.H Nasution was able to escape and run away from the PKI. But unfortunately, the victim of the PKI attack was his daughter, Ade Irma Suryani, who was shot in her mother's arms.